Networking banana and plantain: INIBAP annual report 1997 - International Network for the Improvement of Banana and Plantain (1998)
Summary French and Spanish This report contains focus papers on 3 aspects: (1) PROMUSA - the global programme for Musa improvement; (2) genetic transformation for improvement of bananas; and (3) the banana and its relatives. Reports are also given of thematic activities (Musa germplasm management and improvement) and of INIBAP's activities in Latin America and the Caribbean, Asia and the Pacific, eastern and southern Africa, and West and Central Africa. (Abstract © CAB ABSTRACTS, CAB International)